The Influence of Mechanic and Humanistic Clues on Consumer Loyalty of Nepalese Restaurant Business - Adhikari, Ujjwal (Journal of Business and Management, 2024)
Background: The rapid growth of tourism in areas like Pokhara Valley has fueled significant expansion in the restaurant sector, increasing competition and making customer loyalty vital for sustained success. So, it is essential to examine how factors such as ambiance, decor, aroma (mechanical cues), and staff interactions (humanistic cues) shape consumer experience and loyalty. As demand for diverse food services rises in Nepal, driven by cultural shifts and evolving expectations, these insights are valuable for crafting strategies that build stronger customer relationships in the industry. Objectives: To identify the relationship between mechanical cues and humanistic cues on consumer loyalty in restaurant business along with intermediating role of perceived quality. Methods: This study employed a positivist paradigm with a quantitative research design. A deductive approach guided the research, using established theories and hypotheses. A sample of 300 respondents was selected through convenience sampling from Pokhara residents. Data were collected using a structured questionnaire focused on mechanical and humanistic cues, perceived quality, and consumer loyalty. PLS-SEM was used for analysis, allowing the exploration of relationships between variables and testing the proposed model’s hypotheses. Results: The study found that there is no significant relationship between mechanical cues and perceived quality, indicating that these factors do notably enhance consumer perceptions. Additionally, perceived quality did not mediate the relationship between mechanical cues and consumer loyalty. However, mechanical cues had a significant direct effect on consumer loyalty. Conclusion: The study concludes that while things like atmosphere and decor can directly influence customer loyalty, personal interactions, and quality service are key to retain those customers and maintain a sustainable hospitality business. JEL Classification: M00, M3, M31